2024
DOI: 10.1002/ksa.12082
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐based differences exist in the functional knee phenotypes classification of the osteoarthritic knee

Sabrina Chelli,
Taras Rudyy,
George Mihai Avram
et al.

Abstract: PurposeTo identify gender differences in (1) the coronal alignment of functional knee phenotypes and (2) the JLCA (joint line convergence angle) in relation to the phenotype classification.MethodsThis study is a retrospective data analysis, including 12,099 osteoarthritic knee computed tomography (5025 male, 7074 female) analysed by Medacta software for hip‐knee‐ankle angle (HKA), femoral mechanical angle (FMA), tibial mechanical angle (TMA) and JLCA. The data were grouped into genders and combined according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In a study of 4884 lower limb computed tomography (CT) scans of patients scheduled for TKA, the distal femoral surface orientation varied between 11.0°varus and 15.5°v algus (mean of 2.7°valgus), while the tibial surface orientation ranged between 20.5°varus and 20.5°valgus (mean 2.9°varus) [1]. Moreover, Chelli et al, evaluating 12,099 osteoarthritis (OA) knees CT scans, found that although the most common phenotype was the same for both men and woman, there were gender-based differences in knee phenotype, as well as in hip-knee-ankle angle (HKA), and femoral mechanical angle [6]. Generally, the scientific definition of normality, when a criterion is normally distributed and follows the Gaussian curve, is objectively defined using mean, standard deviation and confidence intervals.…”
mentioning
confidence: 99%
“…In a study of 4884 lower limb computed tomography (CT) scans of patients scheduled for TKA, the distal femoral surface orientation varied between 11.0°varus and 15.5°v algus (mean of 2.7°valgus), while the tibial surface orientation ranged between 20.5°varus and 20.5°valgus (mean 2.9°varus) [1]. Moreover, Chelli et al, evaluating 12,099 osteoarthritis (OA) knees CT scans, found that although the most common phenotype was the same for both men and woman, there were gender-based differences in knee phenotype, as well as in hip-knee-ankle angle (HKA), and femoral mechanical angle [6]. Generally, the scientific definition of normality, when a criterion is normally distributed and follows the Gaussian curve, is objectively defined using mean, standard deviation and confidence intervals.…”
mentioning
confidence: 99%